Comprehensive Comparison of 6-switch Buck-type Rectifier and SWISS Rectifier under Different Modulation Strategies - XIAO Yue; FENG Zhuowen (Kongzhi Yu Xinxi Jishu)
In order to compare the comprehensive performances of three-phase Buck-type converters with different topologies and modulation strategies, and to evaluate their applicability in different fields, two common converters were comprehensively evaluated, including the performances of 6-switch Buck-type rectifier and SWISS rectifier under space vector modulation and carrier modulation. The detailed comparison contained power loss and efficiency, quality of input current, common mode characteristics, reactive power compensation ability, semiconductors, etc. Via this comparative evaluation, performances of the proposed rectifier topologies were introduced on the point of system, which could provide some references for the proper selection of topology and modulation strategy in the practical application.